Application of the Group Investigation Type Cooperative Learning Model in Improving Students' Understanding of Mathematical Concepts - Saraswati, Dewi; Harmilawati, Harmilawati; P, Sudirman (Universitas Islam Ahmad Dahlan (UIAD), 2025)
The purpose of this study is to determine the improvement of the understanding of mathematical concepts of students in the XI class of application at SMK Muhammadiyah Balangnipa through the application of a group investigation-type cooperative learning model. The type of research used in this study is classroom action research (PTK), with a quantitative research approach. The population in this study is all Class XI students at SMK Muhammadiyah Balangnipa totaling 6 people using the total sampling technique in sampling. The data collection techniques in this study are concept comprehension tests, and documentation. The data analysis technique in this study is a prerequisite test consisting of a normality test, a homogeneity test, and a hypothesis test. The application of the group investigation type cooperative learning model provides learning motivation for students, thereby increasing students' understanding of concepts in learning activities. The cooperative learning model of group investigation type is feasible to be applied in the learning process. This is shown from the results of the N Gain Analysis on the understanding of mathematical concepts, namely Frequency in the ineffective category as many as 1 person, fracture in the less effective category is 1 person, frequency in the effective category is 3 people, and frequency in the moderately effective category is 1 person.